Drinking Reasons and Alcohol Problems by Work Venue Among Female Sex Workers in Guangxi, China. (16th April 2015) - Chen, Yiyun; Li, Xiaoming; Shen, Zhiyong; Zhou, Yuejiao; Tang, Zhenzhu
<x xml:space="preserve">Abstract</x> Objective: Alcohol use is a key determinant of sexual risk behaviors, but pathways to alcohol use in the context of commercial sex still remain unclear. The present study explores reasons for drinking and their roles on alcohol use problems among female sex workers (FSWs) in different types of commercial sex venues. Method: In 2009, a sample of 1, 022 FSWs from Guangxi, China completed a survey containing a 10-item Alcohol Use Disorders Identification Test (AUDIT) and a 28-item measure of reasons for drinking. Factor analysis revealed five reasons for drinking: suppression, disinhibition, work requirement, sexual enhancement, and confidence booster. Results: All identified reasons except confidence booster appeared to be related to a higher tendency of developing alcohol use problems among FSWs. Types of commercial sex venues moderated the relationship between work requirement and alcohol use problems. Conclusions: Alcohol-risk reduction interventions among this population need to provide them with alternative approaches to regulate emotions and modify their misconceptions about alcohol's sexual enhancing function. More attention is needed to FSWs' vulnerability to the negative influence of occupational drinking.